2022
DOI: 10.1002/adfm.202207556
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Soluble Cues Enhance Tendon Progenitor Cell Invasion into Injectable Synthetic Hydrogels

Abstract: Synthetic hydrogels represent an exciting avenue in the field of regenerative biomaterials given their injectability, orthogonally tunable mechanical properties, and potential for modular inclusion of cellular cues. Separately, recent advances in soluble factor release technology have facilitated control over the soluble milieu in cell microenvironments via tunable microparticles. A composite hydrogel incorporating both of these components can robustly mediate tendon healing following a single injection. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 73 publications
2
11
0
Order By: Relevance
“…Mouse Achilles tendon explants were encapsulated in the hydrogel system to testify the effect of TPC recruitment. The hydrogel system significantly enhanced TPCs recruitment and induced tenogenic differentiation of TPCs ( Kent et al, 2022 ).…”
Section: Applications Of Hydrogel/stem Cell Therapy In Tendon Repairmentioning
confidence: 99%
“…Mouse Achilles tendon explants were encapsulated in the hydrogel system to testify the effect of TPC recruitment. The hydrogel system significantly enhanced TPCs recruitment and induced tenogenic differentiation of TPCs ( Kent et al, 2022 ).…”
Section: Applications Of Hydrogel/stem Cell Therapy In Tendon Repairmentioning
confidence: 99%
“…In sum, our starPEG-sGAG μGUIDe platform for precision morphogen delivery presents significant advancements over previous approaches 47,12 to locally probe and engineer tissue development. A key advantage of this platform is the far-going tunability of the μGUIDe morphogen affinity achieved through the customizable charge properties (sulfation patterns and concentrations of the incorporated sGAG components), which offers unprecedented options in tailoring morphogen gradient formation with cellular resolution.…”
mentioning
confidence: 93%
“… The dynamic organization of tissue development is reciprocally controlled by localized gradients of morphogens emanating from distinct clusters of cells that act as signaling centers 1 . While microgels 2,3 have shown promise to recapitulate this process in engineered tissue constructs, their capacity to tailor morphogen distribution in space and time remained limited 47 . Here, we introduce a library of sulfated glycosaminoglycan (sGAG)-based microgels that offer unprecedented control over morphogen affinity (μGUIDe, μGel Units to Instruct Development), thus enabling precise formation of concentration gradients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, injectable hydrogels have attracted increasing attention in tissue engineering and translational medicine because of their tunable physicochemical properties in response to the surrounding environment. [19,20] Wu et al reported a mild photothermal GelMA/PMMA/PDA hydrogel platform with beneficial osteogenic ability for bone defect regeneration. [21] Zhou et al constructed a hydrogel platform with tunable stiffness based on magnetic nanoparticles cross-linked GelMA for cartilage regeneration.…”
Section: Introductionmentioning
confidence: 99%